2015
DOI: 10.1007/s10877-015-9705-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in anatomical relationship between vertebral artery and internal jugular vein in children and adults measured by ultrasonography

Abstract: Cannulation of the internal jugular vein (IJV) under ultrasound guidance can reduce complications, such as common carotid artery (CCA) puncture, accidental vertebral artery (VA) puncture. However, these complications still occur, especially in pediatric patients probably due to anatomical predisposition of VA. This study compared differences in anatomical location of VA and IJV between pediatric and adult patients. Children with body weight <20 kg (n = 16) and adults who required central venous or pulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…In a previous pediatric study, the relative size of the right VA to the IJV at the cricoid level measured by ultrasonography was 14% in children <20 kg, and the mean value of the minimal distance between the VA and IJV was 4.3 mm . In our cohort with a similar body weight, the relative size of the VA to the IJV was greater (22.4% and 40.2% on the right and left sides, respectively, at the cricoid level) and the distance between the VA and IJV was greater (mean 6.0 mm in group 1) compared to those in the previous study.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In a previous pediatric study, the relative size of the right VA to the IJV at the cricoid level measured by ultrasonography was 14% in children <20 kg, and the mean value of the minimal distance between the VA and IJV was 4.3 mm . In our cohort with a similar body weight, the relative size of the VA to the IJV was greater (22.4% and 40.2% on the right and left sides, respectively, at the cricoid level) and the distance between the VA and IJV was greater (mean 6.0 mm in group 1) compared to those in the previous study.…”
Section: Discussionsupporting
confidence: 58%
“…Overlapping between the VA and IJV can contribute to the risk of inadvertent VA puncture during IJV catheterization. According to previous studies, about 40%‐82% of pediatric patients showed full or partial overlap between the VA and IJV on the right side . In our study involving chest CT in children at the neutral position, full or partial overlap was observed in 52%‐78% of children.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Accidental puncture of the vertebral artery is another reported complication, as the vertebral artery is proximal to the internal jugular vein in infants and children . Our results indicate that almost all of the vertebral artery lies posteriorly laterally to the internal jugular vein in all planes.…”
Section: Discussionmentioning
confidence: 49%